ANALISIS KEKASARAN PERMUKAAN BAJA SKD-11 PADA PROSES CNC TURNING MENGGUNAKAN METODE TAGUCHI - Rabinaswil Samuel Napitupulu; Robert Napitupulu; Husman Husman (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The machining process achieved with a CNC–Turning type SL25 B/500 based on the minimum surface roughness value, the reason for setting the variables smooth but contrary to the processing time because the longer the machining, the smoother the results. On the other hand, the longer the machining process, the more the costs involved. The research that has been conducted aims to determine the contribution of the CNC Turning process variables type SL-25 B/500 to reduce variations in the response of the workpiece surface roughness. This research also wants to achieve the suitable setting of the work variable of the SL-25 B/500 CNC turning machine to obtain the minimum (smaller is better) using a surfafe roughness test tool. The work variable that we want to work on are spindle rotation, feeding depth, and feeding motion. We determined the experiment design based on the Taguchi method and an orthogonal L18 matrix (21 x 37). Then to avoid interference, replication was carried out 2 times. This research proves the precise and accurate combination of work variable parameter settings to achieve the minimum surface roughness are spindle rotation of 640 put/min, feeding depth of 1 mm, and feeding motion of 0.05 mm/rev. The average of the surface roughness using the initial settings in the 16th combination experiment is 1,362 m.